Towards a greener photovoltaic industry: Enhancing efficiency, environmental sustainability and manufacturing costs through solvent optimization in organic solar cells - Fernando Rodríguez-Mas; David Valiente; Juan Carlos Ferrer; José Luis Alonso; Susana Fernández de Ávila (Heliyon, 2023)
The energy sector is a major contributor to global greenhouse gas emissions, necessitating a transition to renewable energy sources. The photovoltaic industry plays a crucial role in this transition by harnessing solar energy, a clean and abundant resource. However, the high cost of solar panels remains a challenge. Organic solar cells (OSCs) offer a promising alternative to conventional silicon-based cells due to their low production costs and flexibility. In this study, we focus on optimizing the performance of OSCs by investigating the influence of solvent volume in the hole transport layer. By gradually increasing the volume of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and tetrahydrofuran (THF) in the PEDOT:PSS layer, we analyse the impact on power conversion efficiency (PCE) and assess the economic and environmental implications. Our results demonstrate the potential for enhancing the PCE of OSCs through solvent optimization, thereby advancing the greening of the photovoltaic industry while considering economic viability and environmental sustainability.